(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The objectives of this research are to overcome the limitations of rice bran (RB) and de-oiled rice bran (DORB) by fermentation anaerobically using inoculum from the rumen of a canulated sheep for desirable chemical changes. Materials and Methods: Initially, RB and DORB were fermented by 10% rumen liquor for 12 h at 39°C at different moisture levels (10, 20, 30, 40, 50, and 60% phosphate buffer). Again, DORB was fermented for 24, 48, and 72 h at 39°C using 10% rumen liquor at different moisture levels (10, 20, 30, 40, 50, and 60% phosphate buffer). Before and after fermentation, RB and DORB were analyzed for pH, proximate components, neutral detergent fiber (NDF), total-P, inorganic-P, and phytate-P. Results: Fermentation of RB and DORB for 12 h reduced (p < 0.05) pH, crude fiber (CF), NDF, and phytate-P, but increased (p < 0.05) the content of inorganic-P. Subsequent fermentation of DORB for 24, 48, and 72 h reduced pH, CF, and NDF. Total-P of fermented DORB remained similar till 72 h fermentation (p < 0.05). But, inorganic-P increased with the increasing duration (24, 48, and 72 h) of fermentation and increased (30, 40, and 50) moisture level (p < 0.05). Alternatively, phytate-P decreased with increasing duration and moisture level (p < 0.05). Conclusion: Inoculation of rumen microbes and incubation of RB (12 h) and DORB (24 h) at room temperature reduced phytate-P and fiber content (CF and NDF) when the moisture level was up to 50%; those are the indicators to reduce the limitation of RB and DORB to use as feed for nonruminant animals like poultry and pigs. J. Adv. Vet. Anim. Res., 9(4): 728–735, December 2022 http://doi.org/10.5455/javar.2022.i642